Prospective study of accuracy of C-reactive protein and leucocyte count in diagnosis of acute appendicitis in comparison with histopathology - Jaiswal, Anand Kumar; Rai, Rajesh Kumar; Chandra, Abhishek (International Surgery Journal, 2020)
Background: Acute appendicitis is one of the most common surgical emergencies. Approximately 7.0% of the population will have appendicitis in their lifetime with the peak incidence occurring between the age of 10 and 30 years. The classical history of peri umbilical pain at beginning and later shifting to right iliac fossa is present in only 50% cases. C-reactive protein is an acute phase reactant synthesized by liver in response to tissue injury. Serial measurement of CRP can improve the accuracy of diagnosing acute appendicitis. Methods: A prospective study of 70 cases with clinical diagnosis of acute appendicitis admitted in the department of surgery, B. R. D. Medical College Gorakhpur during a period of one year. Results: There was young age predominance (54.2%) and commonest presenting symptom was RIF pain (100%) followed by nausea/vomiting (66%) and fever (60%). Among 48 cases of histopathology proven appendicitis, CRP was raised in 44 cases (91.6%). Conclusions: Serial measurement of CRP is more sensitive and specific than TLC count and the raised value of CRP is directly related to the severity of inflammation. Combining the TLC and CRP increases the diagnostic accuracy and therefore may reduce rate of negative appendectomy.